The Effect of Graphene Nanoplatelets on the Properties of Hybrid Polyamide/Glass Fiber Composites - Andreea Afilipoaei; Zina Vuluga; George-Mihail Teodorescu; Monica Cărăulașu; Augusta Raluca Gabor; Cristian Andi Nicolae; Mihai Cosmin Corobea (Chemistry Proceedings, 2022)
Currently, the method of solving the issues related to the environment has become a topic of great interest and is approached by researching several directions, such as recycling or the replacement of polluting materials [...]